Translating the Biggles stories for Czech readers: a case of moderate transposition. Issue 1 (3rd April 2018) - Orr, Robert
ABSTRACT: Despite their Britocentric orientation, translations of Captain William E. Johns's Biggles stories have been well received outside the United Kingdom. One country where Biggles is quite popular is the Czech Republic. Some passages in Biggles Goes to War, however, set in an invented small Ruritanian-type country located at the eastern edge of Europe, might be seen as causing problems for Czech readers. In her Czech version thereof Alena Petruželková's approach is to transpose the action to somewhere in the Middle East, changing many of the names, while leaving the storyline unchanged, even down to details, and adding a degree of vagueness. Transposition to the Middle East also opens the door to a treatment from the point of view of Orientalism. Following Henry Whittlesey's framework for handling a wide variety of transpositions, this paper will ask whether Petruželková's own transposition has succeeded in preserving the original flavour of Biggles Goes to War . The answer is generally positive, with one or two reservations.